DAMPAK PEMEKARAN KABUPATEN BUTON TENGAH TERHADAP KINERJA INFRASTRUKTUR WILAYAH - Hernila Hernila; La Ode Geo; La Ode Suriadi (Universitas Halu Oleo, 2020)
The purpose of the study is 1) Analyze the development of regional infrastructure before and after division. 2) Analyze public service performance before and after regional combustion. 3) Analyze regional economic growth before and after division. This research is descriptive qualitative and quantitative. The variables used in this study are regional infrastructure including roads, education, health, economy. While economic growth includes Gross Regional Domestic Product (GRDP) and per capita GRDP. Based on the results of the study it can be concluded that expansion has a positive impact on improving regional infrastructure. Public service performance before and after regional expansion where the average ratio of availability of educational facilities to elementary school level, Junior high school and high school, for elementary school level that is equal to 53 schools, Junior high school 54 and 40 high school. Whereas after the expansion there was an increase namely for the elementary school level of 60 schools, Junior high school 68 schools, and 42 high school levels. The availability of health facilities before the expansion of the area namely 16 health facilities and after the expansion has increased amounting to 19 health facilities. Economic growth before was 3.78 percent and after expansion of 5.80 percent, it’s show that was an increase in the economic sector by 2.1 percent. Key Words: Impact expansion, infrastructure performance